Business Aggression, Institutional Loans, and Credit Crisis: Evidence from Lending Practices in Leveraged Buyouts - CAO, Xiaping Jerry (Institutional Knowledge at Singapore Management University, 2009)
This paper investigates the lending practices related to leverage buyouts (LBOs) market between high and low write-down institutions. The write-downs, which are a proxy for business aggression of institutions, are mainly related to credit crisis from the beginning of 2007 to August 10, 2008. We find that high (low) write-down institutions increase (decrease) loan market share dramatically during the period of 2001-2006. The increase is mainly driven by the segment of loans sold to institutional investors, such as collateralized loan obligations vehicle, hedge fund, and insurance companies. Institutional loans originated by high write-down institutions carry significantly fewer covenants and higher interest spread than those by low write-down institutions during 2001-2006. However, there are no such differences during 1995-2000. The aggressive lending practice by high write-down institutions to lower quality borrowers during 2001-2006 appeared to be mitigated by reputable private equity (PE) investors. High write-down institutions arranged loans with more covenants and lower interest spread for borrowers with investments from more reputable private equity investors.